2018
DOI: 10.1016/j.nicl.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

DeepIED: An epileptic discharge detector for EEG-fMRI based on deep learning

Abstract: Presurgical evaluation that can precisely delineate the epileptogenic zone (EZ) is one important step for successful surgical resection treatment of refractory epilepsy patients. The noninvasive EEG-fMRI recording technique combined with general linear model (GLM) analysis is considered an important tool for estimating the EZ. However, the manual marking of interictal epileptic discharges (IEDs) needed in this analysis is challenging and time-consuming because the quality of the EEG recorded inside the scanner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 33 publications
0
46
0
Order By: Relevance
“…Our recent study shows that automatic spike detection can provide comparable and, in some cases, even superior results compared to manual EEG markup in EEG‐fMRI analysis . Similarly, another recent study shows that deep‐learning–based semi‐automatic spike detector can produce EEG‐fMRI results comparable to those of traditional markup methods …”
Section: Discussionmentioning
confidence: 56%
“…Our recent study shows that automatic spike detection can provide comparable and, in some cases, even superior results compared to manual EEG markup in EEG‐fMRI analysis . Similarly, another recent study shows that deep‐learning–based semi‐automatic spike detector can produce EEG‐fMRI results comparable to those of traditional markup methods …”
Section: Discussionmentioning
confidence: 56%
“…Moreover, previous EEG-fMRI studies reported detection of IED-related BOLD changes in 50-60% and 60-70% of the patients with spike-triggered or continuous EEG-fMRI, respectively [45]. The literature also brings into light the possibility of increasing the EEG-fMRI yield to 80-90% through using multiple HRFs peaking at 3, 5, 7, and 9 s to calculate the Page: 136 www.raftpubs.com convolutions [1,10]. It has been wellestablished that neuroelectrical activity and the corresponding hemodynamic response of the physiological and pathological brain function do not overlap precisely.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal autocorrelations are corrected with an autoregressive model of order one [40], and low-frequency drifts are modeled with a thirdorder polynomial. The traditional spike-based model uses the time and duration of each event to build an IED-specific regressor and convolves it with spike related hemodynamic response function, whereas, the current study proposes to convolve the independent component time series with 4 HRF peaking at 3,5,7, and 9 seconds [1]. All components are included in the same general linear model (GLM).…”
Section: Bold Signal Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplest data augmentation method is adding noise to the EEG signal in time domain directly. However, considering the characters of EEG such as low signal-to-noise ratio, non-stationarity and insufficient spatial resolution, this method may destroy EEG signal's feature in time domain [23]. So we propose the method that first transform the EEG recordings to the frequency domain via STFT [24], then add perturbations to amplitudes in frequency domain, finally reconstruct the time-series by inverse STFT.…”
Section: A Data Augmentationmentioning
confidence: 99%